Nutrient use and Response of African Catfish Clarias Gariepinus to Fishmeal diets Containing Auto-Detoxified Mixtures of Jatropha Kernel Cake with Bovine Blood (Global Journal of Science Frontier Research, 2021)
African catfish Clarias gariepinus fingerlings were used as a model to evaluate diets containing three auto-detoxified mixtures of Jatropha kernel cake with bovine blood (ADMJKC/bb) ingredients. The test ingredients and a control were used to produce seven isonitrogenous and isocalorific diets in which they either replaced 30% or 50% level of fishmeal. The Jatropha kernel cake mixed with bovine blood at a ratio of 2:1; heated, spread dried, remoistened and substituting 30% of fishmeal, and the Jatropha kernel cake mixed with bovine blood at a ratio of 3:1; unheated, spread dried, without remoistening, and substituting 30% of fishmeal), were similar to the control in feed conversion ratio and feed cost per gram of gain.
Keywords: auto-detoxified; jatropha -kernel -cake bovine -blood; clariasgariepinus